The plight and promise of mental health providers in the face of a warming planet: Perspectives and experiences from the Philippines - Aruta, John Jamir Benzon R; Salcedo, Sena S; Guilaran, Johnrev; Guinto, Renzo R * (Taylor and Francis Group, 2022)
A growing body of research shows the inimical impact of climate change on people’s mental health. However, attention to mental health providers at the frontlines is rather sparse, especially in climate-vulnerable countries. This commentary aims to present the perspectives and experiences of mental health providers within the context of climate change in the Philippines. Specifically, this paper explicates the challenges faced by mental health providers in trying to address the increasing climate-related distress experienced by many Filipinos and the recent progress in promoting climate change and mental health nexus in the country. The recommendations offered in this commentary will hopefully provide the basis for a more comprehensive mental health framework that incorporates climate change and supports mental health providers in their pursuit to preserve Filipino mental health on a warming planet.